2013
DOI: 10.4155/cli.13.63
|View full text |Cite
|
Sign up to set email alerts
|

Study design considerations for evaluating the efficacy and safety of pancreatic enzyme replacement therapy in patients with cystic fibrosis

Abstract: In 2006, the US FDA issued a ‘Guidance for Industry’ regarding submission of New Drug Applications for pancreatic enzyme replacement therapy (PERT) products. Five oral delayed-release PERT products have been approved by the FDA, and several others are under development and/ or evaluation for New Drug Application submission. We present in this paper recommendations of the Cystic Fibrosis Foundation's Cystic Fibrosis (CF) Therapeutics Development Network and Data Safety Monitoring Board regarding study design co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…9,33 The current analysis was based on data from a relatively brief 1-week study interval, but this conforms to recommendations that studies that evaluate the efficacy and safety of PERT should utilize placebo-controlled periods of 6 to 8 days. 34 In addition, long-term outcomes with pancrelipase treatment in patients with EPI after pancreatic resection were recently reported 35 ; patients who received pancrelipase in the 1-year openlabel extension study demonstrated sustained reductions in CFA that were significant compared with pretreatment values. Changes in glucose control and intensity of DM treatment (eg, insulin use and plasma glucose levels) before and after pancrelipase treatment were not recorded during the trial.…”
Section: Discussionmentioning
confidence: 94%
“…9,33 The current analysis was based on data from a relatively brief 1-week study interval, but this conforms to recommendations that studies that evaluate the efficacy and safety of PERT should utilize placebo-controlled periods of 6 to 8 days. 34 In addition, long-term outcomes with pancrelipase treatment in patients with EPI after pancreatic resection were recently reported 35 ; patients who received pancrelipase in the 1-year openlabel extension study demonstrated sustained reductions in CFA that were significant compared with pretreatment values. Changes in glucose control and intensity of DM treatment (eg, insulin use and plasma glucose levels) before and after pancrelipase treatment were not recorded during the trial.…”
Section: Discussionmentioning
confidence: 94%
“…8 Male and female subjects with CF followed at 1 of 9 CF Foundation-accredited centers were selected for this study. Subjects were eligible if they were $12 years of age, had a diagnosis of CF based on standard criteria, 9 and had documented EPI with a fecal elastase less than 50 mg/g.…”
Section: Methodsmentioning
confidence: 99%
“…During these confinements, subjects received blue marker capsules (FD&C blue #2) at the start and end of a 72-hour controlled diet, consisting of 85-115 g fat/day and a minimum of 1.5 to 2 g of protein/kg body weight. All stool was collected after the appearance of blue stool following the 1st blue dye capsules until the appearance of blue stool due to the second blue dye capsules, and analyzed for weight, fat content, and nitrogen content [9][10][11].…”
Section: Trial Designmentioning
confidence: 99%